Prophetic Leadership and Its Contribution to Building Religious Character - Purwanto, Muhammad; Kholid, Idham; Meriyati, Meriyati; Septuri, Septuri; Koderi, Koderi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to understand how village heads apply prophetic leadership in building religious character in Panca Jaya District, Mesuji Regency, Lampung. To understand the phenomena in the field, the researcher uses a qualitative case study approach. The data collection technique is done through interviews, observation, and documentation. Since being in the field, the data analysis was conducted concerning the Milles and Huberman concept. The results showed that the prophetic leadership applied by the village head was displayed through humanist leadership through amar ma’ruf nahi munkar, liberation leadership, and transcendence leadership. This study implies the importance of leaders to have the ability to interact, communicate and socialize in carrying out a clear vision to gain the trust of the community.